SAS-Oriented Pop Up Book Interactive Media: Developing the Beginning Reading Ability of Grade Elementary School Students - Putri, Winda Fitria Supriyanto; Sutama, S (Universitas Muhammadiyah Surakarta, 2023)
SAS-oriented pop up book interactive media encourages the development of elementary school students’ initial reading skills. There are two objectives of this research are. To describe the process of using SAS-oriented pop up book interactive media. To explore the growth and development of initial reading skills in grade 1 elementary school students. The overall type of research is research and development. This research is qualitative ethnography. The research subjects were the principal, class 1 homeroom teacher, and class 1 students of Tunggulsari II State Elementary School, Surakarta. Data collection techniques are interviews, observation and documentation. Data validity uses triangulation of sources and methods. Data analysis technique uses flow method. There are two research results in this article as follow. The process of using SAS-oriented pop up book interactive media in beginning reading in grade 1 has good potential for developing beginning reading skills. The growth and development of elementary school students’ initial reading abilities shows that in stage 1 the initial reading abilities of grade 1 students are relatively low. Meanwhile, in stage 2, the application of SAS-oriented pop up book interactive media was declared successful and met the criteria for developing initial reading skills in grade 1 elementary school students.